EVALUASI KUALITAS KERJASAMA AKADEMIK UIA DENGAN MITRA - Iffah Budiningsih; Efridani Lubis (Akademika : Jurnal Teknologi Pendidikan, 2018)
The aim of this cooperation is the evaluative research to know the level of effectiveness and efficiency of the implementation of UIA cooperation with partners, so that the results can be used to repair either substance and the implementation of cooperation in the future. Evaluation methods using survey with samples as many as 65 people were taken simple random from a population of 168 target fixed lecturer in UIA TA 2017/2018. Data analysis using descriptive with SPSS program. The result of this research show that opinions of the fixed lecttures about the quality of cooperation with partners from both the domestic and overseas: highly optimum = 1.5%;, Optimum = 44.7%; moderate optimum = 36.9%; less than optimum = 15.54% and very less than optimum = 1.5%. The average opinion of the respondents = 3.23 score , that means the quality of collaboration with UIA partners shows quality of